B2O3‐modified geopolymer and its liquid‐phase sintered products for immobilization of strontium. Issue 2 (6th September 2022) - Jia, Lingyu; He, Peigang; Jia, Dechang; Yuan, Jingkun; Cai, Delong; Li, Daxin; Duan, Xiaoming; Yang, Zhihua; Zhou, Yu
Abstract: Sr‐containing ceramic products produced from geopolymer, (Na, Sr)‐GP, have been reported as excellent candidate materials for the immobilization of radionuclide 90Sr, despite sintering temperature at 1200°C. In this work, the product possessing the best immobilization performance (leaching rate of 1.29% for Sr 2+ ) can be produced at 1000°C in the method of liquid‐phase sintering via the addition of fluxing agent B2 O3 at 2.0 wt% in the geopolymer precursor. The mechanical properties of the geopolymer precursor (Na, Sr)‐GP were also enhanced via the promotion role of B2 O3 to geopolymerization. It was revealed that the overall anti‐leaching ability of the Sr‐containing ceramic product not only depends on the microstructure of the loading substrate but also can be affected by the chemical state of radioactive strontium retention in the loading matrix.